Hyperspectral above-water radiometric quantities observed during cruise SO267/2 aboard RV SONNE - Shungudzemwoyo Pascal Garaba; Daniela Voß; Oliver Zielinski (PANGAEA, 2020)
Automated continuous above-water hyperspectral calibrated radiometric quantities were observed in the international waters of the Pacific Ocean during the scientific field campaign SO267/2 aboard RV SONNE. The cruise began on 28 January 2019 from Suva, Fiji and finished on 14 February 2019 in Manzanillo, Mexico. A radiometer setup with two TriOS RAMSES-ACC hyperspectral cosine irradiance meters to measure incoming solar irradiance, four TriOS RAMSES-ARC hyperspectral radiance meters to measure total upward sea surface leaving radiance Lsfc at 45° nadir and sky-leaving radiance Lsky at 45° zenith angle were installed using a custom-made frame at the bow of RV SONNE. The frame was attached to the bow of the ship with the radiance meters having a 90° azimuthal angle separating them or 45° from the ship heading/bow. Quality control involved retaining the Lsfc observations with lowest values (Garaba et al., 2012; Garaba et al., 2015). Data logging was automated using TriOS MSDA XE version 8.9.2 software and further processing was done using Mathworks Matlab 2016a and R software. Processed data was interpolated to 1 nm spectral resolution using PCHIP function in Matlab between 320 and 950 nm. Raw data is available on request.